Electrodeposited Co-Doped Fe3O4 Thin Films as Efficient Catalysts for the Oxygen Evolution Reaction - Han, Shan; Liu, Suqin; Yin, Shengjie; Chen, Lei; He, Zhen (Electrochimica acta, 2016)
The development of highly active electrocatalysts at a low cost is essential to the process of generating hydrogen fuel through electrochemical and photoelectrochemical water splitting. Here, we report a comprehensive investigation of the one-step electrodeposited cobalt-doped magnetite (CoxFe3-xO4, 0<x<1) thin films as active and stable OER catalysts in alkaline solutions. The CoxFe3-xO4 thin film electrode can be fabricated in minutes or even tens of seconds. The Co-doping concentration, thickness, and orientation of the CoxFe3-xO4 films can be simply controlled by varying the deposition potential, deposition time, and the substrate, respectively. The dependences of the catalytic activity of the CoxFe3-xO4 films on the composition, thickness, and orientation of growth are explored. The CoxFe3-xO4 films exhibit greatly enhanced catalytic activities toward the OER compared to the Fe3O4 thin film. The polycrystalline CoxFe3-xO4 film deposited at −0.88VAg/AgCl for 150seconds exhibits the highest catalytic activity with an overpotential of ∼0.42V at a current density of 10mAcm−2, a Tafel slope of 53mVdec−1, and an exchange current density of about 2.39×10−10Acm−2, which are comparable to those of Co3O4. Besides, the CoxFe3-xO4 films possess good stability during the long-term electrolysis at a current density of 10mAcm−2 in 1M NaOH. The satisfactory catalytic activity and stability combined with the simplicity of fabrication make the electrodeposited CoxFe3-xO4 films economically and environmentally preferable compared to Co3O4 as catalysts for the oxygen evolution reaction.